Pyrolyzer Modification for Making Coconut Shell Charcoal with Isolation from a Mixture of Clay, Sand, and Rice Straw - Adi, Tegar Trikora; Youfa, Rita; Rahmad, Dedy; Akli, Khairul (invotek, 2024)
Currently, many charcoal makers use drums as pyrolyzers, this is because the oxygen (O2) entering the combustion chamber is controlled, the oxygen level entering the combustion chamber must be low so that the shell does not burn out. The aim of this research is to calculate the heat loss rate of the pyrolyzer for making coconut shell charcoal and to analyze the effect of a mixture of clay, sand and rice straw insulator on the charcoal yield and quality of the charcoal produced. This research focuses on reviewing pyrolyzer modifications based on aspects of mixed variations of clay, sand and rice straw insulating materials in dealing with heat loss. Testing of furnace performance is carried out using comparisons of several parameters or components including temperature, time and insulator material. The final stage of the research is to draw conclusions and draw conclusions based on the results of material variations and the factors that influence them. The research results show that the best insulator is the TP3 pyrolyzer with an insulator mixed with clay, sand and rice straw in a ratio of 2:1:0.3 with a heat loss of 7,378.992 W and ΔT of 195°C. The addition of rice straw to a mixture of clay and sand insulators provides significant benefits in increasing ΔT and reducing heat loss. The addition of rice straw to a mixture of clay and sand insulators has a significant impact on the carbonization process of coconut shell charcoal. Even though the charcoal yield decreases with the addition of rice straw to the insulator, the quality of the charcoal produced increases, especially in terms of fixed carbon content with the best insulator being the TP3 pyrolyzer with a carbon content value of 78.54%.